Volunteering on Heritage at Risk sites and wellbeing: A qualitative interview study - Julie Pattinson; Despina Laparidou; Joseph Akanuwe; Anna Scott; Claudia Sima; Carenza Lewis; Niro Siriwardena (Wiley, 2023)
Abstract Introduction We explored experiences of volunteering in Heritage at Risk (HAR) projects, intended to mitigate the deterioration to historic assets, and the relationship with wellbeing. We aimed to understand the value of HAR to volunteers' wellbeing and relationships between HAR programme characteristics such as location, asset type and type of activity. Methods We used a qualitative design with semi‐structured interviews of a purposive sample of volunteers recruited via Historic England (HE), employing Systematic Grounded Theory involving open, axial and selective coding. Findings We interviewed 35 volunteers (18 male and 17 female) participating in 10 HAR projects. We identified six themes from the data analysis. (1) Purpose-was associated with volunteering motivations; there were some barriers to volunteering and many types of facilitators, including accessibility to local heritage sites. (2) Being-volunteers showed an appreciation and attachment to their place of residence. (3) Capacity-to learn heritage‐specific skills and diversify experiences in learning new skills (life, technical and personal). (4) Sharing-community engagement, connectedness, and inclusivity captured diversity and inclusion within volunteers across age, ethnicity, ability, and gender. (5) Self‐nurture-HAR volunteering created physical, psychological, and social benefits with limited risks and adverse outcomes. (6) Self‐actualisation-described volunteers reflecting on their experiences. Conclusion HAR volunteering was associated with positive physical, social and psychological wellbeing outcomes. The study provides an evidence base for specific wellbeing benefits of volunteering at Heritage at Risk sites, although we could not conclude that HAR project activity was the cause of increased wellbeing. Public Contribution Staff from HE were involved in designing the project brief. In selecting the HAR project sites, we took advice and recommendations from HE staff across all their six regional offices.